Effect Of Location And Type Of Water Sprays For Respirable Dust Suppression On A Continuous-Mining Machine - Joseph E. Matta (The National Institute for Occupational Safety and Health (NIOSH), 1976)
The Bureau of Mines conducted a field study to investigate thin suppression of respirable dust by water sprays on a continuous-mining machine. Determining the importance of the top and bottom sprays for two types of spray nozzles was emphasized. Results showed, at a 90-pct confidence level, that (1) at least 70 pct of the dust was generated during the sump cut, even though nearly half of the coal was mined during the downshear operation, (2) the water sprays on the top of the boom had little effect in suppressing respirable dust, and (3) B.D. 5 spray nozzles mounted beneath the boom reduced dust at least 33 pet more than B.D. 5 sprays mounted on top of the boom. A single-cut technique was developed that gave good reproducibility for replicate cuts (coefficient of variation of 20 pct).